Corporate Liability in Environmental Crimes: A Comparative Study of Indonesian and Islamic Criminal Law - Rodia, Harahap; Ramadani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
Background: Environmental degradation resulting from corporate and individual actions remains a persistent legal challenge in Indonesia. Despite the existence of regulatory frameworks such as Law No. 32/2009 on Environmental Protection and Management (as amended), enforcement remains weak—particularly in corporate-related crimes, as exemplified by the H₂S gas leak incident in Mandailing Natal.. Purpose: This study investigates criminal liability for environmental crimes from the perspectives of Indonesian positive law and Islamic criminal law.. Methods: Using a normative legal research method supported by comparative and case approaches, the study examines legal texts, jurisprudence, and relevant Islamic legal doctrines within the framework of maqāṣid al-sharī‘ah. Results: Findings suggest that while Indonesian law provides sufficient formal basis for corporate prosecution, its implementation lacks consistency. In contrast, Islamic criminal law, through ta‘zīr principles, offers a moral-ethical framework emphasizing justice, deterrence, and ecological responsibility. Implication: The study highlights the urgency of integrating ethical-legal principles from Islamic jurisprudence into the existing legal system to ensure more equitable environmental justice. Originality: This paper’s novelty lies in its contextual application of maqāṣid-based reasoning to corporate environmental crimes